2017
DOI: 10.1038/ejhg.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Personal utility in genomic testing: a systematic literature review

Abstract: Researchers and clinicians refer to outcomes of genomic testing that extend beyond clinical utility as 'personal utility'. No systematic delineation of personal utility exists, making it challenging to appreciate its scope. Identifying empirical elements of personal utility reported in the literature offers an inventory that can be subsequently ranked for its relative value by those who have undergone genomic testing. A systematic review was conducted of the peer-reviewed literature reporting non-health-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(160 citation statements)
references
References 59 publications
(49 reference statements)
5
155
0
Order By: Relevance
“…However, psychiatry researchers often used the concept to refer to opportunities for not just medical but also psychosocial and behavioral preparation or modification. There is a body of literature that supports that the general public values genomic information not just for its direct medical implications, but for its “personal utility” or its value for nonmedical reasons such as enhancing capacity to cope with health risks and ability to plan finances, housing and long‐term care (Kohler, Turbitt, & Biesecker, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, psychiatry researchers often used the concept to refer to opportunities for not just medical but also psychosocial and behavioral preparation or modification. There is a body of literature that supports that the general public values genomic information not just for its direct medical implications, but for its “personal utility” or its value for nonmedical reasons such as enhancing capacity to cope with health risks and ability to plan finances, housing and long‐term care (Kohler, Turbitt, & Biesecker, ).…”
Section: Discussionmentioning
confidence: 99%
“…Receiving a genetic diagnosis may also have “personal” utility, defined as benefits valued by patients that reach beyond clinical utility . Although reactions are not universal, many families report benefits such as reducing guilt, helping to set expectations about prognosis, informing reproductive decisions, and providing an opportunity to connect with others with the same genetic cause.…”
Section: Return Of Results Workhopmentioning
confidence: 99%
“…Receiving a genetic diagnosis may also have "personal" utility, defined as benefits valued by patients that reach beyond clinical utility. 47,48 Although reactions are not universal, many families report benefits such as reducing guilt, helping to set expectations about prognosis, informing reproductive decisions, and providing an opportunity to connect with others with the same genetic cause. In a recent study that assessed motivations for genetic testing among members of families containing multiple individuals with epilepsy, "the potential to know if epilepsy in the family is caused by a gene" ranked second highest, reflecting a strong influence of personal utility in motivations for testing.…”
Section: Key Pointsmentioning
confidence: 99%
“…Survey items for round 1 were developed based on the findings from a systematic literature review of personal utility . The systematic review was conducted specifically in preparation for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Survey items for round 1 were developed based on the findings from a systematic literature review of personal utility. 16 The systematic review was conducted specifically in preparation for this study. The review identified elements of personal utility that were reported in the empirical literature, focusing on the concept as defined by participants or patients.…”
Section: Roundsmentioning
confidence: 99%